2021
DOI: 10.1021/acs.macromol.1c01628
|View full text |Cite
|
Sign up to set email alerts
|

Melting Kinetics of Superheated Polymer Crystals Examined by Isothermal and Nonisothermal Fast Scanning Calorimetry

Abstract: Quantitative analyses of the melting kinetics of superheated polymer crystals, including the isothermal analysis of the time dependence of melting and nonisothermal analysis of the heating-rate dependence of melting, were carried out by fast scanning calorimetry on linear polyethylene that has a narrow melting temperature region. The time evolution of the decrease in the total crystallinity during melting was modeled using a first-order kinetic equation with a rate coefficient, which defines a characteristic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…However, after annealing at 140 °C for a long time (e.g., 720 and 1440 min), X s tends to a constant of ≈10%. Such an incomplete melting phenomenon, which is consistent with the study reported by Toda and co-workers, [9] is not caused by insufficient annealing (the details can be seen in Supporting Information and Figure S5, Supporting Information). On account of the survived crystal remnants, X s is assumed to decay with modified Debye relaxation [21] as given by…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, after annealing at 140 °C for a long time (e.g., 720 and 1440 min), X s tends to a constant of ≈10%. Such an incomplete melting phenomenon, which is consistent with the study reported by Toda and co-workers, [9] is not caused by insufficient annealing (the details can be seen in Supporting Information and Figure S5, Supporting Information). On account of the survived crystal remnants, X s is assumed to decay with modified Debye relaxation [21] as given by…”
Section: Resultssupporting
confidence: 91%
“…Melting of semicrystalline polymer strongly depends on the crystallization history [1][2][3][4] and displays complex behaviors, such as a broad melting temperature range, [5,6] parallel occurrence of melting, and recrystallization, [7,8] as well as superheating-dependent melting kinetics. [9,10] For long-chain polymers, crystallization from highly entangled melts generally leads to a semicrystalline state with alternating layer-like lamellar crystals and entangled amorphous layers. [11][12][13] The entanglements of the polymer restrict the chain mobility in the amorphous phase and influence the metastability of the polymer crystals indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…The above-described experimental observations fit the general view of melting of crystals slightly above the temperature of their formation and reorganization/recrystallization of the unstable melt to form crystals of higher stability, which then melt at a correspondingly higher temperature. More specifically, the shift of the low-temperature melting peak to a higher temperature with increasing heating rate is caused, besides a thermal lag, by the kinetics of the melting process, that is, its time dependence, with fundamental information about the melting kinetics of polymers available in the literature. The smallness of the low-temperature melting peak is assumed to be caused by overlapping melting-related endothermic heat flow and recrystallization-related exothermic heat flow, as outlined in earlier work (see, e.g., Figure 9 in ref ). Simultaneously, with increasing heating rate, recrystallization of the melt is suppressed/slows down, which is best recognized by the increasing area of the low-temperature peak and decreasing area of the high-temperature melting peak.…”
Section: Resultsmentioning
confidence: 97%
“…The observation of a single melting event on heating PBS at a high rate of 20 000 K/s reveals furthermore that only a single-crystal population formed on crystallization at 40 °C. The melting temperature observed on heating at such a high rate, however, is affected by a thermal lag and the kinetics of melting, both shifting the melting process during scanning to a higher temperature. , To obtain the true zero-entropy-production melting temperature ( T m,ZEP ), thermal-lag correction and extrapolation to zero heating rate (HR) are needed, which conveniently can be done by fitting the observed heating-rate-dependent melting temperatures ( T m ) with eq , as suggested in the literature where τ is the thermal lag and z is an adjustable parameter, describing the melting kinetics and being dependent on the crystallization temperature, , that is, on the morphology of crystals. It is expected to be between 0 and 0.5, with higher values indicating a lower activation barrier of the melting process.…”
Section: Resultsmentioning
confidence: 99%
“…From an experimental point of view, melting can be monitored thought different approaches. For example, differential scanning calorimetry detects this transition by identifying the associated latent heat, atomic force and polarized optical microscopies by tracking the shrinkage of crystals, and X-ray scattering and infrared spectroscopy by following the evolution of structural order. , Focusing on the kinetic character of the transition, experimental and theoretical efforts have been so far dedicated to understand the energetic contributions leading to the breakdown of the crystalline lattice, the consequent detachment and diffusion of chain stems, and their relation to chain folding. Albeit the extensive work, the molecular origin of melting is still not clear. Because of the lack of experimental probes capable of tracking trajectories of molecules during this transition, nothing is known regarding how spontaneous fluctuations, the microscopic origin of the molecular mobility, lead to the formation of the liquid phase.…”
mentioning
confidence: 99%